Study of demand-oriented teaching strategy for nursing students in the Central Sterile Supply Department (以护生需求为导向的消毒供应中心实习护生带教策略研究) - ZHANG Tianqiang (张天强); CHEN Huiying (陈慧颖); FU Li (付立) (中西医结合护理, 2022)
Objective To investigate the nursing students’ demand for required knowledge about disinfection and supply before internship and during the clinical rotation, and establish a demand-oriented teaching strategy for nursing students in the Central Sterile Supply Department. Methods Totally 14 nursing students participating in the internship program in the Central Sterile Supply Department were recruited by a convenient sampling method. Questionnaire-based survey was conducted at first day and the end of internship, respectively. The survey data was analyzed. Results The main demands for required knowledge about disinfection and supply included instruments packaging (n=14), working procedure (n=12 ) and instruments identification (n=14). The main demands for required knowledge during the clinical rotation included selection of disinfection methods (n=9), instruments packaging (n=10), surveillance of sterilization quality (n=14), preservation of aseptic instrument (n=14) and identification of instruments in sterility pack(n=14). The most popular teaching methods were one-on-one teaching (n=14), video-assisted teaching (n=13) and manual book (n=14). Conclusion It is required to establish a demand-oriented teaching strategy, which is based on the demand analysis of required knowledge about disinfection and supply before internship and during the clinical rotation, for nursing students in the Central Sterile Supply Department. (目的 调查了解护生对消毒供应知识的需求及医院轮转过程中接触到的消毒供应相关知识现状, 探讨建立消毒供应中心护生带教策略模式。方法 通过便利抽样法选取2020年3月份以来在消毒供应中心实习的14名护生, 采用自制问卷进行调查。在入科当天, 调查护生消毒供应知识入科需求; 轮转结束后, 调查护生在轮转过程中接触到的消毒供应相关知识与带教方式。结果 护生入科前对消毒供应知识需求主要包括器械打包(14人)、工作流程(12人)、器械识别(14人); 护生在轮转过程中接触到消毒供应知识主要为物品消毒灭菌方法选择(9人)、物品包装(10人)、灭菌质量监测(14人)、无菌物品保存(14人)、无菌包内器械配置与识别(14人)等内容, 最喜欢的带教方式为“一对一”带教(10人) 、视频教学(13人) 、科室手册(14人)。结论 应将护生对于消毒供应知识需求和轮转过程中接触到的消毒供应相关知识纳入到护生带教中, 以护生需求为导向, 为消毒供应中心护生带教内容制定与带教方法。)